E-168 Analysis of same-procedure recordings of cerebral venous pressure and cerebrospinal fluid opening pressure in idiopathic intracranial hypertension patients. (23rd July 2022) - Ryu, B; Ballout, A; White, T; Patsalides, A
Abstract : Introduction/Purpose: Idiopathic intracranial hypertension (IIH) is a potentially devastating neurological disorder that results from the rise in intracranial pressure and is diagnosed by cerebral venous pressure (CVP) recordings, cerebrospinal fluid opening pressure (CSF-OP) greater than 25cm H2 O, papilledema, and neuroimaging. At our institution, albeit not routinely, it is common practice to measure the CVP and perform a lumbar puncture (LP) to record the CSF-OP when performing a diagnostic venogram of IIH patients. In addition, follow-up venograms and LPs will be performed to record CVP and CSF-OP from the same procedure. Given the strictly controlled environment when recording CVP and CSF-OP, we aimed to study the relationship between CVP and CSF-OP in IIH patients. Materials and Methods: Following institutional review board approval, the medical records of IIH patients between 2020 to 2021 were reviewed. Those patients who received venous manometry for CVP and LP for CSF-OP during the same neurointervention were included in the study. Patient were then divided into pre-VSS and post-VSS cohorts. Demographic information, CVPs (mmHg) from superior sagittal sinus (SSS), transverse sinus (TS), and sigmoid sinus (SS), and CSF-OP (cmHg) were collected. The trans-stenotic gradient (TSG) was calculated as the difference in pressure between TS and SS. Regression analysis was conducted using the F-test for linear regression model using SSS CVP and TSG to predict CSF-OP. Results: 37 IIH patients were included in the study- 22 patients in the pre-VSS cohort and 15 patients in the post-VSS cohort. All of the patients were female with a mean age of 37 years (STD: 12) and BMI of 36 (STD: 8). The majority of patients had stenosis in the right side (27/37) of the venous sinus system. For the pre-VSS cohort, both TSG and SSS CVP were significantly correlated to CSF-OP (p<0.005). BMI served as a negative control, and it was not significantly correlated to CSF-OP (p>0.1). For the post-VSS cohort, TSG and SSS CVP were not correlated to CSF-OP (p>0.1). This is attributed to the TSG, SSS CVP, and CSF-OP all decreasing after VSS to within normal limits of pressure. SSS CVP was significantly decreased in post-VSS patients compared to those of pre-VSS patients (SSS 13.4 vs 29.2, p<0.001), while that of SS did not change (11.3 vs 12.9, p>0.05). Furthermore, the TSG of the stenosed side significantly reduced in post-VSS patients compared to that of pre-VSS patients (0.9 vs 14.8, p<0.001). CSF-OP was significantly decreased in post-VSS patients compared to that of pre-VSS patients (18.5 vs 31.6, p<0.001). Conclusion: CVP and CSF-OP are significantly correlated in IIH patients; therefore, either recording may provide sufficient evidence for IIH. VSS in IIH patients significantly reduces the pathologically elevated SSS CVP, which also resolves the TSG. Elevated CSF-OPs in IIH patients were also significantly resolved after VSS. CVP, TSG, and CSFOP are valuable in understanding the pathophysiology, diagnosis, and management of IIH. Disclosures: B. Ryu: None. A. Ballout: None. T. White: None. A. Patsalides: None.